THE THEME OF HOSPITALITY IN PINDAR'S FOURTH PYTHIAN*. (25th March 2015) - Unknown
Abstract : The relevance of Pindaric myth to its literary and historical context is a problem presented by many of Pindar's odes. In the case of Pythian 4 it is the plea for the return of Damophilus that has proved difficult to relate to the myth of the Argonautic expedition – so much so, that some scholars have denied that any connection exists between the myth and this part of the ode. Those who seek to establish a correlation between the myth and the plea have, for the most part, considered parallels between the relationship, circumstances, and character traits of Jason and Pelias and those of Arcesilas and Damophilus. The limitations, however, of looking for exact correspondence are generally acknowledged. Carey in particular postulates that Pindar 'simply presents in the myth a number of themes, any or all of which may be applied to the situation in Cyrene'. It is the contention of this article that the theme of hospitality, as it develops in the myth, is central to understanding the relevance of the myth to the plea for Damophilus.